Nilai Kearifan Lokal dalam Perilaku Politik Studi Analitis tentang Etika dan Sikap Berpolitik Santri di Madura - Mohammad Suhaidi; Sihabuddin Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2020)
The advantage of Islamic Boarding politicians is their ability to preserve the typical Islamic characteristics values; those are ethics and modesty towards the Kiai and Ulama as their teachers. The majority of the Madurese people make Ulama as a role model. Obedience to the Kiai is a form of respect that becomes the identity of Santri, including santri who are involved in practical politics. The uniqueness of santri (santri politicians) when determining the political decision cannot be separated from the blessing from the Kiai, even though they participated in different political party The Kiai's blessing is essentially a political capital that can strengthen its existence in the political competition.The characteristics of santri are to remain istiqomah in the making of local wisdom value as the basis of politics. Buppa 'Bappu', Gurur, ratoh has become an integral part of every political taken step. Getting the blessing from the Kiai who has been united in pesantren becomes a necessity made by bhindara. There are two things to get the blessing from Kiai, First, a direct approval from Kiai by acabis or sowan to the Kiai.Second, an approval through Kiai's sons, by communicating to the Kiai's son about his political choice.